Injectable radiopaque and bioactive polycaprolactone‐ceramic composites for orthopedic augmentation. Issue 7 (28th November 2014) - No, Young Jung; Roohani‐Esfahani, Seyed‐Iman; Lu, Zufu; Schaer, Thomas; Zreiqat, Hala
Abstract: The aim of this study was to develop and characterize an injectable bone void filler by incorporating baghdadite (Ca3 ZrSi2 O9 ) particles (average size of 1.7 µm) into polycaprolactone (PCL). A series of PCL composites containing different volume percentages of baghdadite [1 (PCL‐1%Bag), 5 (PCL‐5%Bag), 10 (PCL‐10%Bag), 20 (PCL‐20%Bag), and 30 (PCL‐30%Bag)] were prepared, and their injectability, setting time, mechanical properties, radiopacity, degradation, and cytocompatibility were investigated. PCL, PCL‐1%Bag, PCL‐5%Bag, and PCL‐10%Bag were able to be injected through a stainless steel syringe (Length: 9.0 mm, nozzle diameter: 2.2 mm) at 75°C at injection forces of below 1.5 kN. The core temperature of the injected material at the nozzle exit ranged between 55 and 60°C and was shown to set after 2.5–3.5 min postinjection in a 37°C environment. Injection force, melt viscosity, and radiopacity of the composites increased with increasing baghdadite content. Incorporation of 10–30 vol % baghdadite into PCL increased the compressive strength of the composites from 36 to 47.1 MPa, compared with that for pure PCL (31.4 MPa). Similar trend was found for the compressive modulus of the composites, which increased from 203.8 to 741 MPa, compared with that for pure PCL (205 MPa). Flexural strain of PCL, PCL‐5%Bag, and PCL‐10%Bag exceeded 30%, and PCL‐10%Bag showed the highest flexural strength (29.8 MPa). Primary human osteoblasts cultured on PCL‐10%Bag showed a significant upregulation of osteogenic genes compared with pure PCL. In summary, our results demonstrated that PCL‐10%Bag could be a promising injectable material for orthopedic and trauma application. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1465–1477, 2015.